Three-dimensional MobileMT and TMI Data Inversions for Mineral Exploration ... - Michael S. Zhdanov; Alex Gribenko; Alexander Prikhodko; Henrik E. Sabra; Michael Jorgensen; Leif H. Cox (Zenodo, 2024)
MobileMT is gaining popularity among airborne methods due to its penetration depth and greater sensitivity to resistors. TMI data are also collected simultaneously with the MobileMT survey. While this method uses natural sources processed to apparent resistivities similar to standard magnetotelluric data, the interpretation of the MobileMT data requires dedicated inversion algorithms to most accurately produce resistivity models of the earth. This paper introduces the novel MobileMT and TMI data modelling and inversion methods and their application for mineral exploration. The important, distinguished feature of these methods is that they can be applied to the spatially large-scale problems typical for airborne geophysics data by employing the concept of moving sensitivity domain. Airborne MT and TMI data are inverted in 3D to produce volume distributions of the rock formations' electrical resistivity and magnetic properties, including induced and remanent magnetizations. The developed 3D inversion methods ...